Mobile learning (m-learning) at the university in time of COVID-19: A training tool in Higher Education - Loayza Maturrano, Edward Faustino (2022)
The objective of the research was to analyze the use of mobile learning and technologies based on it as a training tool in the university educational process; and propose uses and applications of m-learning. The study methodology performed descriptive and inferential statistical analysis of the application of a survey applied to 74 university students from four universities (public and private) on the use of mobile devices. The results show that university students use mobile devices for leisure and recreation activities rather than for learning and knowledge. It is concluded that the relative majority of those surveyed are not used to using mobile devices on a daily basis as a learning tool or to search for information.